Sexing the body: Gender politics and the construction of sexuality - Fausto-Sterling, Anne (Basic Books, 2000)
Discusses the causes and determining factors of gender behavior differences and sexual identity, particularly biology and societal expectations, and argues that differences between male and female are not always distinct.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme matérialiste; genre; histoire et politique; hétérosexisme; injustices épistémiques; philosophie politique; premier cycle; production des savoirs; ressource en ligne; sciences humaines; sciences sociales; sex3383; sexe/genre; sexualité; sociologie; systèmes d'oppressions; thématiques; épistémologie

L'invention du naturel : les sciences et la fabrication du féminin et du masculin - Gardey, Delphine; Löwy, Ilana.. (Histoire des sciences, des techniques et de la médecine, 2000)
Comprendre ce que sont les hommes et les femmes, penser la différence entre les sexes a constitué et constitue encore un objet d'investigation et un enjeu politique et social de premier ordre. Des sciences d'hier à celles d'aujourd'hui, des discours et des pratiques médicales aux plus récentes sciences humaines, les auteurs de cet ouvrage révèlent la fragilité des évidences dites sur la nature ou le corps des femmes et des hommes, et insistent sur la force des arrangements et organisations du social qui ont pu en découler. Plus qu'une enquête descriptive sur les états variables des représentations proposées par les sciences, il s'agit d'analyser comment les scientifiques " en société " élaborent les critères de différenciation entre les sexes, contribuant à faire endosser à la nature certaines formes de domination. Convié à découvrir, en France et à l'étranger, l'histoire récente de ces nouveaux terrains d'enquête, le lecteur est aussi invité à méditer sur les effets de longue durée d'une modernité occidentale instaurée sous le signe de l'altérité entre raison et nature, hommes et femmes.
Keywords: approches et analyses; cours; discipline; discours dominant; essentialisation; genre; histoire et politique; identité sexuelle; naturalisation; premier cycle; production des savoirs; rapports sociaux de sexe; sciences; sciences humaines; sciences sociales; sex3383; sexe/genre; sociologie; systèmes d'oppressions; thématiques; épistémologies féministes

Experiments in knowing: Gender and method in the social sciences - Oakley, Ann (The New Press, 2000)
Ann Oakley came to widespread attention as part of the new school of British feminists to emerge in the 1960s, and has since earned a reputation as one of the most innovative feminist thinkers and social scientists writing today. In Experiments in Knowing, a major new work, Oakley integrates her personal and professional thinking to examine the historical development of methodology in the social and natural sciences, demonstrating how both fields have been subject to a process of "gendering." Oakley not only reconciles the long-standing opposition between the quantitative and the qualitative methods but shows that the experimental and intuitive approaches must be used in tandem to provide a full understanding of any subject of scientific inquiry. Written in accessible language, Experiments in Knowing addresses themes of common interest across such diverse fields as social policy, education, health, and women's studies. Certain to generate considerable debate, it is both a fascinating history of the practice of social science from a feminist perspective, as well as an argument for a new way of thinking about our ways of knowing.
Keywords: 1900-1999; approches et analyses; cours; discipline; europe; fem1000; genre; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sciences sociales; thématiques; théories féministes; épistémologie

Questionnements féministes et méthodologie de la recherche - Ollivier, Michèle; Tremblay, Manon (Collection Outils de recherche, 2000)
La recherche féministe repose-t-elle sur une éthique de la recherche qui lui est propre, Est-elle mieux servi par les méthodes qualitatives que quantitatives ? Comment arrive-t-elle à concilier engagement politique et effort d'élaboration d'un discours vrai sur le monde ? Cet ouvrage présente quelques éléments essentiels de la réflexion féministe actuelle sur la méthodologie de la recherche en sciences humaines et sociales.
Keywords: approches et analyses; canada; cours; cycles supérieurs; discipline; discours; fem1000; fem7000; har4600; justice sociale; méthodologie; point de vue situé; premier cycle; pédagogie; sciences humaines; sciences sociales; thématiques; épistémologie

Carnal appetites: food, sex, identities - Probyn, Elspeth (Routledge, 2000)
n Carnal Appetites, Elspeth Probyn charts the explosion of interest in food - from the cults that spring up around celebrity chefs, to our love/hate relationship with fast food, our fetishization of food and sex, and the impact of our modes of consumption on our identities. 'You are what you eat' the saying goes, but is the tenet truer than ever? As the range of food options proliferates in the West, our food choices become inextricably linked with our lives and lifestyles. Probyn also tackles issues that trouble society, asking questions about the nature of appetite, desire, greed and pleasure, and shedding light on subjects including: fast food, vegetarianism, food sex, cannibalism, forced feeding, and fat politics.
Keywords: approches et analyses; care; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sexualité; thématiques; études de genres